The Effectiveness of Remediation Learning Strategy in Reducing Misconceptions on Chemistry: A Systematic Review - Islamiyah, Kafita Krisnatul; Rahayu, Sri; Dasna, I Wayan (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2022)
Misconceptions are defined as wrong ideas or views of a person's concept different from the scientific concepts formulated by experts in their field. It must be reduced immediately so as not to hinder the process of understanding the next interconnected matter. Reducing students' misconceptions can be done through remedial learning. This study aimed to describe the phase in processing information that causes students' misconceptions based on learning theory, describe the implementation of an effective remedial learning strategy to reduce misconceptions in chemistry, and describe learning media that can be integrated into remedial learning in chemistry. The method used in this study was the systematic literature review (SLR) by searching articles on the electronics journal database. The database used in this study was ERIC, Google Scholar, and Sinta from 2011 to 2021. Seventeen articles were found in 14 indexed journals (Scopus and Sinta). The data was analyzed by collecting the related articles, reducing them based on the research focus, displaying the data, and concluding. The result showed that students build their understanding through assimilation and accommodation. The disequilibrium between both of these aspects causes a misconception. It must be reduced immediately through remedial learning. Six remedial learning strategies can reduce misconceptions in chemistry effectively, i.e., POE, Guided Inquiry, MRCD, Ember, Conceptual Learning, and ECIRR. This effectiveness is due to the phase of creating cognitive conflict. Integrating Information and Communication Technology (ICT) interactive media in implementing remedial learning strategies has a positive impact because interactive media can visualize abstract concepts. Hence, the cognitive accommodation phase is more effective.